The quantitative assessement of the location of building projects in a territory - Ginevičius, R. (Journal of Civil Engineering and Management, 1995)
In many research works concerning the dispersion of building projects the influence of this dispersion on organizational structures of building enterprise management has not been almost touched upon. However, the territorial concentration of production is one of the most important structural factor. The quantitative evaluative analysis allows us to answer the question: why is there no common oppinion on this problem? The main reason is that the fields and aims of applying this factor by various researchers are different.When the dispersion is considered as a structural factor, it's index must reflect the influence of dispersion on the organizational structure of the enterprise management. The index may be represented by the number of building sitez or the amount of work per territorial unit.Article in Lithuanian.Statybos objektų sklaidos kiekybinis įvertinimasFirst Published Online: 26 Jul 2012